CEO gender and managerial entrenchment. (c2017) - Kebbe, Reem Walid (2017)
This paper investigates the effect of gender on managerial authority and control over firms. Though the percentage of female CEOs is very low, it has been steadily increasing throughout the 1996-2014. Our findings suggest that accounting performance, CEO age, and board size reduce the likelihood of appointing female managers. On the other hand, the appointment of female CEOs is directly associated with the percentage of female directors and board independence. In addition, this paper proposes that female managers are more entrenched as compared to male managers. We show that the presence of women managers decreases the turnover-performance sensitivity, increases the E-index, and inflates CEO compensation. While women face more obstacles to be at the top of corporations than men, those achieving such positions seem to possess specific characteristics enabling them to gain authority and control over firms.